Peran Komunikasi Pariwisata Pada Kegiatan Penghargaan Top Muslim Friendly Destination 2023 - Wahyuni, Siska; Nuraeni, Yeni (Jurnal Pustaka Komunikasi, 2024)
This study aims to determine the implementation of knowledge, development and success of Muslim Friendly Destination of Indonesia through Tourism Communication that generates motivation and appreciation. In the development of a tourism sector that is friendly to Muslim tourists, the role of tourism actors, academics, stake holders and the community is needed. It is not an easy matter to motivate various groups in the development of Muslim-friendly tourism, it requires the active role of all parties who can realize the development of Muslim-friendly tourism through tourism communication. The research method used is qualitative descriptive using Burhan Bungin's tourism communication theory, motivation theory and appreciation theory. The results of this study show that Indonesia's success in winning the Top Muslim Friendly Destination of the Year 2023 award cannot be separated from the role of tourism communication embodied by marketing communication management. The form of motivation in the award can be seen through recognition, appreciation and achievement of self-actualization or institutions in this case Muslim-friendly tourist destinations and appreciation of various groups both from within the country and abroad.